Happy Finding joy in every day and letting go of perfect - Cotton, Fearne; Arthur, Liam; Gardiner, Ben (London Orion Spring, 2017)
Happiness, you gorgeous warm ray of sunshine. I love it when you spring up out of nowhere and take me by surprise and how you can make clouds part and corners of mouths lift ?? Fearne Cotton understands how important happiness is, and why we need to seek it out each and every day. Determined to help break the taboo around mental health, here - for the first time - she opens up honestly about her own battle with depression, and the little things that help keep it at bay so she can continue trekking towards the good stuff. Including expert advice from Mind, and packed with little ideas and practical exercises so you can join in, she invites you to pick up your pencil and come on this journey with her ?
The Sunday times bestseller
Keywords: Happiness